HIV-infected adolescents on anti-retroviral therapy: a retrospective descriptive cohort study of breast abnormalities documented during routine care - Dunlop, Jackie (My University, 2017)
Background: HIV antiretroviral therapy (ART) is associated with breast abnormalities in adults, especially efavirenz (EFV). Little is known about the prevalence of these adverse effects among adolescents receiving ART. Methods: A retrospective record review describing breast conditions in adolescents receiving ART at three facilities in Johannesburg, South Africa was conducted. Patients aged 10-19 years who presented from 1 January to 31 December 2014 were included. Analyses were conducted to determine whether EFV use was associated with an increase in breast conditions. Results: A total of 631 patient records were reviewed, 37 (6%) had an abnormal breast event documented of whom 24/37 (65%) were male. Patients with abnormal breast conditions developed them 1.5 years later than patients with normal breast development (p<0.0005). Forty-one abnormal breast events were observed in thirty-seven patients with twenty being described as gynaecomastia or lipomastia (49%). 44% had concurrent generalised lipodystrophy (n=19). Of those with an abnormal breast event, 71% of patients had CD4 counts >500 cells/μl and were virologically suppressed (n=29). Those on EFV had a significantly higher prevalence of breast abnormalities compared to other regimens (p=0.016) and all had been exposed to EFV before. No other ART drug was associated with breast abnormalities in this cohort. Sixteen patients had substitution of EFV and three breast events resolved once substituted from EFV. Breast abnormalities in adolescents on ART Conclusion: Six percent of patients had an abnormal breast condition in this study. Use of EFV and increasing age were associated with breast abnormalities in this population. Further research is needed to better understand this phenomenon.
A research report submitted in submissible format to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of MSc in Child Health (Community Paediatrics) 20 June 2017
Keywords: HIV; Antiretroviral Therapy